Design and Analysis of Capacitive Power Transfer System with and without the Impedance Matching Circuit - F.K.A. Rahman; Shakir Saat; Yusmarnita Yusop; Huzaimah Husin; Y. Aziz (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents the design and analysis of a relatively new wireless power transfer technique using capacitive coupling, named Capacitive power transfer (CPT). In general, CPT system has been introduced as an attractive alternative to the former inductive coupling method. This is because CPT uses lesser number of components, simpler topology, enhanced EMI performance and better strength to surrounding metallic elements. In this work, aluminium sheet is used as a capacitive coupling at transmitter and receiver side. Moreover, a Class-E resonant inverter together with π1a impedance matching network has been proposed because of its ability to perform the dc-to-ac inversion well. It helps the CPT system to achieve maximum power transfer. The CPT system is designed and simulated by using MATLAB/Simulink software. The validity of the proposed concept is then verified by conducting a laboratory experimental of CPT system. The proposed system able to generate a 9.5W output power through a combined interface capacitance of 2.44nF, at an operating frequency of 1MHz, with 95.10% efficiency. The proposed CPT system with impedance matching network also allows load variation in the range of 20% from its nominal value while maintaining the efficiency over 90%.